Sport, Social Exclusion and the Forgotten Art of Researching Poverty: Book Review of Sport and Social Exclusion (2nd ed.). By Mike Collins and Tess Kay. New York: Routledge, 2014, 320 pp.; ISBN: 978-0-415-56880-7. - Haudenhuyse, Reinhard (2015)
Book Review of Sport and Social Exclusion (2nd ed.). By Mike Collins and Tess Kay. New York: Routledge, 2014, 320 pp.; ISBN: 978-0-415-56880-7.